A Local Health Situation Room for COVID-19: Recommendations for Decision-Making From a Higher Education Institution in Mexico - Igor Martín Ramos Herrera; Diana Core Romero Lozano; Adolfo López Corona; José Francisco Muñoz Valle; José Francisco Muñoz Valle; Miguel Ernesto González Castañeda; Héctor Raúl Pérez Gómez; Marina de Jesús Kasten Monges; Moisés Ramos Solano; Norma Alicia Ruvalcaba Romero; Fabian Alejandro Pérez Ávila; Patricia Yokogawa Teraoka; et al. (Frontiers Media S.A., 2021)
Introduction: The Situation Room is a physical or virtual space where experts systematically analyze information to characterize a health situation, especially during emergencies. Decision-making processes are made toward solving health needs and promoting collaboration among institutions and social sectors. This paper presents the context and circumstances that led the University of Guadalajara (UdeG) to install a local health situation room (HSR) to address the COVID-19 pandemic at this institution based in the state of Jalisco, Mexico, a narrative is also made of its working processes and some of its results.Methods: The design of this situation room for COVID-19 was based on the methodology established by the Pan American Health Organization (PAHO)/WHO. This local-type situation room was installed on February 12, 2020. The health problem was characterized, and strategic lines, objectives, and goals were established; the first analysis was derived from an action plan deployed at the UdeG. The strategic lines were situational diagnosis, preventive actions, and containment strategies.Results: The situation room influenced the activities of the UdeG before the epidemic cases started in the state. One of the actions with the greatest impact was developing a mathematical model for predicting COVID-19 cases. Subsequently, new models have been developed according to the epidemiological evolution of the disease, helping manage the epidemic in the state. Another important result was the early closing of face-to-face university activities, reducing contagion risks and the mobility of more than 310,000 students, faculty, and administrative personnel throughout Jalisco.Conclusions: A consequence of the closure was that the confinement generated by the pandemic was the change to virtual meetings from April 2020 to date; but at the same time, this working format was a strength, since it influenced the decision of the university board to change all the academic activities to virtual format before other educational, economic, and social activities in the state did. By April 2020, the situation room transcended its institutional boundaries and was invited to participate at the Jalisco State's Health Committee. Its recommendations have helped to maintain the state with one of Mexico's lowest COVID-19 incidence and mortality rates.